Persepsi terhadap implementasi kebijakan kurikulum MBKM Di IAIN Kerinci: Perspektif dosen dan mahasiswa - Tiara Tiara; Hendra Lardiman (SAP (Susunan Artikel Pendidikan), 2025)
This research aims to discern the perceptions of the academic community at IAIN Kerinci regarding the implementation of the MBKM curriculum, which commenced in the academic year 2023/2024. The research is a descriptive quantitative study. Data were obtained through a survey involving 171 respondents, comprising lecturers and students. The findings indicate that the faculty and students’s perception of the MBKM curriculum implementation at IAIN Kerinci is fairly positive, with an average respondent achievement index of 76.69%. This suggests that the faculty and students support this curriculum implementation as it offers greater flexibility for students to acquire learning experiences. The implementation of this curriculum provides increased opportunities for adaptation and innovation in delivering academic services to students.